Analysis of Factors Affecting the Effectiveness of Public Services in the Digital Era - Velayati, Muhammad Fadillah; Ahmad, Badu (IHSA Institute, 2024)
The digital era has changed the way public services are delivered, but its effectiveness depends on a variety of factors. This study uses a qualitative approach to analyze these factors, combining literature review with interviews with public service stakeholders. The study identifies three main factors influencing the effectiveness of digital public services: infrastructure and technological readiness, human resources and organizational culture, and regulations and policies. Adequate technology and digital readiness are critical, as are skilled government employees and a culture that supports innovation. Flexible regulations and supportive policies are also necessary for the success of digital public services. Research shows that increasing the effectiveness of public services in the digital era requires a holistic approach that focuses on infrastructure, human resources, and regulations. This has important implications for policymakers in developing sustainable digital transformation strategies for public services